Krüppel-Like Factor 6 Splice Variant 1: An Oncogenic Transcription Factor Involved in the Progression of Multiple Malignant Tumors - Hu, Kang; Zheng, Qing-Kang; Ma, Rui-Jie; Ma, Chao; Sun, Zhi-Gang; Zhang, Nan (Frontiers in Cell and Developmental Biology, 2021)
Krüppel-like factor 6 (KLF6) is one of the most studied members of the specificity protein/Krüppel-like factor (SP/KLF) transcription factor family. It has a typical zinc finger structure and plays a pivotal role in regulating the biological processes of cells. Recently, it has been considered to play a role in combatting cancer. Krüppel-like factor 6 splice variant 1 (KLF6-SV1), being one of the alternative KLF6 splicing isoforms, participates in tumor occurrence and development and has the potential to become a new target for molecular targeted therapy, although its action mechanism remains to be determined. The purpose of this article is to provide a comprehensive and systematic review of the important role of KLF6-SV1 in human malignant tumors to provide novel insights for oncotherapy.